Comparison of Cephalometric Measurements Obtained with Conventional and Digital Methods and their Reproducibility - Anshu Kalra; Shirish Goel; Manish Thadani; R M Shetty; Divya Kalra; Savita Lodam (Wolters Kluwer Medknow Publications, 2010)
Aims and objectives: The purpose of the study was to compare the intraobserver reproducibility of cephalometric measurements obtained with digital cephalograms traced with software and equivalent hand-traced conventional cephalograms. Further, the cephalometric measurements obtained with both methods were compared to know any significant differences. Materials and methods: The sample consisted of pretreatment digital and conventional cephalograms of 40 patients (20 males and 20 females). Eleven cephalometric landmarks were identified and 10 measurements calculated by one operator, both manually and with digital tracing software. Intraobserver reliability was assessed for both methods by duplicating the tracings at two weeks interval and using Pearson's correlation coefficient. Further paired "t" test was used to compare the conventional and digital methods. Results: The analysis of error (correlation coefficient) on both methods showed a high correlation of repeated measures. Results indicate that the reliability of repeated measurements appears to be slightly better with conventional radiographs. In the comparison between two methods, statistically significant differences (p < 0.005) were detected for S of the 10 measurements evaluated (Wits. Sn-GoGn, PP-GoGn, U1-L1, L1-GoGn). However, three of these statistically significant results were highly significant (p < 0-001) of Wits, U1-L1, L1-GoGn. Conclusion: Intraobserver reproducibility was found to be better with conventional cephalometric tracings than with monitor displayed digital image tracings. The differences, however, were clinically insignificant. Therefore, computerized cephalometric measurement using direct digital imaging is inherently preferable for its user-friendly and time saving characteristics.